Chinese Human Rights and the Liberal World Order - Hossien Karimifard (حقوق بشر)
Most scholars and researchers interested in China have researched about economic development, foreign policy, competition and cooperation between China and the United States and other major powers, and various scenarios for the transfer of power from the United States to China. An area that has received little attention is the issues related to democracy and human rights in China. The purpose of writing this article is to examine issues related to the place of human rights in domestic law and the country's approach to international legal order based on liberalism. The question of this article is: what components is China's approach to the liberal human rights order in the world based? The hypothesis of this article, which tries to prove it using analytical and explanatory methodology, is that China emphasizes the conditions and characteristics of each country by criticizing the liberal human rights order and the dual policy of the West. China's human rights order stems from the Beijing Consensus on multinational relations, economic relations between actors, and political differences and national and regional cultural diversity. From the perspective of China's executive elite, the common framework of this order is not based on homogenization and globalization that lead to hegemony, but on the simultaneous recognition of commonalities and differences between global actors.